The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1097/mpg.0000000000002184
|View full text |Cite
|
Sign up to set email alerts
|

Are All Breast‐fed Infants Equal? Clustering Metabolomics Data to Identify Predictive Risk Clusters for Childhood Obesity

Abstract: Objectives: Fetal and early life represent a period of developmental plasticity during which metabolic pathways are modified by environmental and nutritional cues. Little is known on the pathways underlying this multifactorial complex. We explored whether 6 months old breast-fed infants could be clustered into metabolically similar groups and that those metabotypes could be used to predict later obesity risk. Methods: Plasma samples were obtained from 183 breast-fed infants aged 6 months participating in the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
0
7
0
3
Order By: Relevance
“…De Luca et al aimed to compare breast-milk composition of obese versus normal-weight mothers. In their cross-sectional observational study, they found a higher amount of leptin in breast milk of obese mothers, whereas breast milk was not different in terms of protein, lipid, and carbohydrate composition and volume [ 137 , 138 ]. Leptin content has also been positively correlated with higher weight gain in infants and increased adiposity as far as 12 months of lactation.…”
Section: Maternal Lifestyle and Nutritional Status During Pregnancmentioning
confidence: 99%
“…De Luca et al aimed to compare breast-milk composition of obese versus normal-weight mothers. In their cross-sectional observational study, they found a higher amount of leptin in breast milk of obese mothers, whereas breast milk was not different in terms of protein, lipid, and carbohydrate composition and volume [ 137 , 138 ]. Leptin content has also been positively correlated with higher weight gain in infants and increased adiposity as far as 12 months of lactation.…”
Section: Maternal Lifestyle and Nutritional Status During Pregnancmentioning
confidence: 99%
“…Kirchberg et al grouped plasma metabolomic profiles of breastfed infants using Bayesian agglomerative clustering 27 . Clustering was predominantly determined by the levels of phosphatidylcholines and sphingomyelins, which suggests that lipoprotein metabolism was an important determinant 27 . Differences in human milk fatty acid composition may also have contributed to the differentiation between clusters.…”
Section: Fat Content and Lipid Speciesmentioning
confidence: 99%
“…Predictive metabolomics-At one extreme of the predictive use of metabolomics is research that looks at metabolomic profiles in children (e.g.,-children who were breast-fed versus those that were not) [108], to determine if there is a signature present at a young age that could be used to predict some later aspect of health and development. The reports of prospective use of these kinds are markers are varied in scope, but a small sampling of the literature finds studies that indicate that there are also signatures that contain predictive markers of the progression of amyotrophic lateral sclerosis [109], bone mass in menopausal women [110] and a proclivity towards the development of major depression [87].…”
Section: Procedural Testingmentioning
confidence: 99%